Effects of adding high-intensity training during an 8-week period on maximal oxygen uptake in 12-year-old youth athletes - Grendstad, H.; Hallén, J. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Purpose Maximal oxygen uptake (VO2max) increases during adolescence parallel to the increase in fat-free mass (FFM). How much endurance training adds to this effect is still controversial. Our aim was to investigate if inclusion of high-intensity training (HIT) during an 8-week training period was superior to low-intensity strength and coordination training in 12-year-old youth athletes concerning the effect on VO2max.